Joseph P. Kennedy: A Life and Times - Koskoff, David E. (Prentice-Hall, Inc. Englewood Cliffs, New Jersey, 1974)
An aura of the legendary surrounded Joseph P. Kennedy ever since the Irish Catholic businessman turned his back on Al Smith and entered the circle of that Protestant aristocrat Franklin D. Roosevelt in the early 1930s. Since then a great number of myths and half truths have revolved around him. While he made great effort to avoid the public eye after the mid 1950s, his absence from the press became conspicuous. The Presidential candidacy of John F. Kennedy in 1960 renewed interest in his father, which was only wetted by the failure of the press to follow the elder Kennedy's doings. Delves into Kennedy's controversial business dealings and political career in addition to his role as a family man.
Includes index
Keywords: Kennedy, Joseph Patrick -- 1888 - 1969